Kajian Perubahan Penggunaan Lahan dan Kesesuaiannya Dengan Rencana Tata Ruang Wilayah (RTRW) Kabupaten Rejang Lebong Berbasis Sistem Informasi Geografis dan Penginderaan Jauh - Alan Kurnia Setiawan; Sri Rahayu (Teknik PWK (Perencanaan Wilayah Kota), 2018)
Rejang Lebong Regency has problems with Land Use (LU) change, which has an impact on increasing space utilization. The rise of this issue has led to cases of spatial violation, namely the existence of LU that aren’t in accordance with Regional Spatial Plan (RTRW). This study aims to examine LU change in Rejang Lebong in 2005-2016 and its suitability with Rejang Lebong RTRW 2012-2032. The method used in this study’s descriptive quantitative with Geographic Information System and Remote Sensing based analysis technique. The result shows that the LU change in 2005-2016 was 55,336,17 Ha, of which 86.75% of it were in accordance with RTRW, while 13.25% of it weren’t in accordance with RTRW. Result of research indicate there’re 374,77 Ha of it located in disaster prone area, that’s in Sindang Kelingi District, Sindang Dataran, Bermani Ulu, Bermani Ulu Raya and Binduriang. In the area of settlement 299.96 Ha of them lies in the steep slopes whose characteristics aren’t suitable as it. This discrepancies, particularly those occurring in protected areas, can’ve a negative impact on the sustainability of nature and increase the vulnerability of communities in the event of a disaster. This’s because there’re new settlement areas developing in protected areas.